2021
DOI: 10.3390/jcm10194456
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probiotics, Prebiotics, and Synbiotics on Uremic Toxins, Inflammation, and Oxidative Stress in Hemodialysis Patients: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: The dysbiosis of gut microbiota may cause many complications in patients with end-stage renal disease, which may be alleviated by probiotic, prebiotic, and synbiotic supplementation. The aim of this systematic review and meta-analysis was to assess the effects of these supplementations on circulatory uremic toxins, biomarkers of inflammation, and oxidative stress in hemodialysis patients. We searched the EMBASE, MEDLINE, Web of Science, and Cochrane Library databases until 8 August 2021. Randomized controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 46 publications
(34 reference statements)
3
12
0
Order By: Relevance
“…Increased oxidative stress elevates the risk of chronic diseases, such as cardiovascular and end-stage renal disease, as it is related to the onset and progression of these adverse conditions [ 11 , 12 , 62 , 63 ]. A greater antioxidant intake has been previously related to a lower risk of disease mortality [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased oxidative stress elevates the risk of chronic diseases, such as cardiovascular and end-stage renal disease, as it is related to the onset and progression of these adverse conditions [ 11 , 12 , 62 , 63 ]. A greater antioxidant intake has been previously related to a lower risk of disease mortality [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…All metabolic processes generate reactive oxygen species (ROS), which can induce oxidative damage to tissue and cell constituents such as lipids, proteins, and nucleic acids [ 1 , 2 ] when left unbalanced. Indeed, the overproduction and accumulation of large amounts of ROS lead to oxidative stress [ 3 , 4 , 5 ], which represents a major contributor to the risk, onset, and progression of chronic diseases [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. A key component of oxidative stress implicated in adverse health effects is lipid peroxidation of polyunsaturated fatty acids and the subsequent production of malondialdehyde (MDA) (a major indicator of lipid oxidation) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A dysbiosis in FD patients with renal impairment might further be triggered by an increased urea secretion into the digestive system, contributing to circulating uremic toxins, systemic inflammation, oxidative stress, cardiovascular events, and other complications as observed in patients with end-stage renal disease (ESRD). 53 …”
Section: Pathophysiology and Potential Mechanismsmentioning
confidence: 99%
“…MDA is a low-molecular-weight solution that participates in oxidative stress, connecting with the progress of CKD and its cardiovascular complications ( 51 ). Seven randomized controlled trials were introduced in the study of Nguyen et al ( 14 ), who found that MDA was significantly reduced in hemodialysis patients after taking three supplements. Several studies also have demonstrated that synbiotics might increase the expression of the antioxidant gene SOD and GPX in the gut by targeting gut bacteria to activate oxidative stability ( 52 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, their efficacy in reducing various indexes has not yet been determined. For example, a meta-analysis from March et al ( 13 ) evaluated the effects of pro/pre/syn-biotics and found a significant reduction in indoxyl sulfate (IS), whereas another meta-analysis ( 14 ) reported these supplements have potential benefits to decrease p-Cresyl sulfate (PCS) instead IS in hemodialysis patients. To our knowledge, the available evidence may not provide a consistent conclusion among the three supplements.…”
Section: Introductionmentioning
confidence: 99%